Is the neonatal creatine phosphokinase level a reliable marker for fetal hypoxia?. Issue 1 (12th November 2016) - Muraoka, Mitsue; Takagi, Koichiro; Morita, Yoshihiro; Nagano, Hiroaki; Henmi, Nobuhide; Hasegawa, Hisaya
Abstract: Aim: The creatine phosphokinase (CPK) level is believed to increase in neonatal peripheral blood after tissue damage, including damage from perinatal hypoxia. However, it is not clear whether it is truly a reliable marker for fetal hypoxia. We investigated the chronological changes in neonatal CPK and the reliability of CPK as a marker for fetal hypoxia. Methods: Sixty term neonates admitted to the neonatal intensive care unit at Tokyo Women's Medical University Medical Center East from April 2009 to April 2010 were enrolled in this study. We evaluated whether asphyxia and fetal heart rate (FHR) abnormality could predict the neonatal CPK level by using receiver–operator curve analysis. We also compared umbilical cord blood pH levels with neonatal CPK levels. In addition, we investigated factors that influence neonatal CPK in non‐asphyxia cases. Results: The median value of CPK peaked on day 1. There were no significant differences in CPK levels regardless of the presence of asphyxia or FHR abnormality. Non‐asphyxiated neonates with older gestational ages and amniotic fluid abnormalities had significantly higher levels of CPK. Conclusion: Our results indicate that the neonatal CPK level is not an appropriate marker for retrospectively predicting either asphyxia or FHR abnormality. There are influencing factors other than asphyxia that increase neonatal CPK. Therefore, one should be careful when making a diagnosis of perinatal hypoxia based solely on increased levels of neonatal CPK after birth.